Long non‐coding RNA as a novel biomarker and therapeutic target in aggressive B‐cell non‐Hodgkin lymphoma: A systematic review - Khanmohammadi, Shaghayegh; Fallahtafti, Parisa (Journal of cellular and molecular medicine, 2023)
Cancer initiation and progression have been associated with dysregulated long non‐coding RNA (lncRNA) expression. However, the lncRNA expression profile in aggressive B‐cell non‐Hodgkin lymphoma (NHL) has not been comprehensively characterized. This systematic review aims to evaluate the role of lncRNAs as a biomarker to investigate their future potential in the diagnosis, real‐time measurement of response to therapy and prognosis in aggressive B‐cell NHL. We searched PubMed, Web of Science, Embase and Scopus databases using the keywords “long non‐coding RNA”, “Diffuse large B‐cell lymphoma”, “Burkitt's lymphoma” and “Mantle cell lymphoma”. We included studies on human subjects that measured the level of lncRNAs in samples from patients with aggressive B‐cell NHL. We screened 608 papers, and 51 papers were included. The most studied aggressive B‐cell NHL was diffuse large B‐cell lymphoma (DLBCL). At least 79 lncRNAs were involved in the pathogenesis of aggressive B‐cell NHL. Targeting lncRNAs could affect cell proliferation, viability, apoptosis, migration and invasion in aggressive B‐cell NHL cell lines. Dysregulation of lncRNAs had prognostic (e.g. overall survival) and diagnostic values in patients with DLBCL, Burkitt's lymphoma (BL), or mantle cell lymphoma (MCL). Furthermore, dysregulation of lncRNAs was associated with response to treatments, such as CHOP‐like chemotherapy regimens, in these patients. LncRNAs could be promising biomarkers for the diagnosis, prognosis and response to therapy in patients with aggressive B‐cell NHL. Additionally, lncRNAs could be potential therapeutic targets for patients with aggressive B‐cell NHL like DLBCL, MCL or BL.